Kegiatan preservasi preventif di Museum Zoologi Sekolah Ilmu dan Teknologi Hayati Institut Teknologi Bandung - Abdillah, Zilki Tsani; CMS, Samson; Khadijah, Ute Lies Siti (Faculty of Communication, Padjadjaran University, 2024)
Zoological Museum, School of Life Sciences and Technology, Bandung Institute of Technology has a collection that includes more than 2,200 specimens, consisting of various types of vertebrates and invertebrates. This collection is of great importance as a means of education, research, and the preservation of biodiversity. The ITB Zoological Museum carries out preventive preservation to maintain condition and sustainability, as well as prevent damage to the collection. This activity encompasses the processes of identifying and storing the collection, arranging the placement and labeling of the collection, and periodically maintaining the collection. This research aims to examine the preservation process in the collections at the ITB Zoological Museum in order to protect and maintain information in the collections and speed up the search for information on fauna collections that have been stored in the form of photos and videos on the ITB Zoological website. This research uses a case study method with a qualitative approach to understand the collection preservation process at the ITB Zoological Museum from the curator's perspective. Data were collected through in-depth interviews, observation, and a literature study. The research results show that the preservation of the collection at the ITB Zoological Museum is carried out in several stages. First, the identification and storage of the collection, where the curator identifies the type, condition, and potential damage to the collection, which is then stored according to its type. Second, the arrangement of placement and labeling of the collection to facilitate the identification process. Third, the maintenance of the collection is carried out periodically by the curator, which includes cleaning, inspecting, and caring for the collection according to its type to prevent further damage. Preventive preservation is a very important activity to maintain the sustainability of the collection at the ITB Zoological Museum. The curator plays a crucial role in the implementation of this preventive preservation and must have adequate knowledge and skills to carry it out.